Ddhd1 knockout mouse as a model of locomotive and physiological abnormality in familial spastic paraplegia. Issue 2 (26th February 2021) - Morikawa, Takuya; Ohishi, Hiroaki; Kosaka, Kengo; Shimojo, Tomofumi; Nagano, Akihiro; Taniguchi, Itsuki; Fujioka, Ryuta; Moriyama, Kosei; Unoki, Motoko; Takahashi, Masatomo; Nakao, Motonao; Izumi, Yoshihiro; et al.
Abstract: We have previously reported a novel homozygous 4-bp deletion in DDHD1 as the responsible variant for spastic paraplegia type 28 (SPG28; OMIM#609340 ). The variant causes a frameshift, resulting in a functionally null allele in the patient. DDHD1 encodes phospholipase A1 (PLA1 ) catalyzing phosphatidylinositol to lysophosphatidylinositol (LPI). To clarify the pathogenic mechanism of SPG28, we established Ddhd1 knockout mice ( Ddhd1 [−/−]) carrying a 5-bp deletion in Ddhd1, resulting in a premature termination of translation at a position similar to that of the patient. We observed a significant decrease in foot–base angle (FBA) in aged Ddhd1 (−/−) (24 months of age) and a significant decrease in LPI 20:4 ( sn -2) in Ddhd1 (−/−) cerebra (26 months of age). These changes in FBA were not observed in 14 months of age. We also observed significant changes of expression levels of 22 genes in the Ddhd1 (−/−) cerebra (26 months of age). Gene Ontology (GO) terms relating to the nervous system and cell–cell communications were significantly enriched. We conclude that the reduced signaling of LPI 20:4 ( sn -2) by PLA1 dysfunction is responsible for the locomotive abnormality in SPG28, further suggesting that the reduction of downstream signaling such as GPR55 which is agonized by LPI is involved in the pathogenesis of SPG28.